Immunoaffinity Purification of Factor VIII Complex - Hornsey, V S; Griffin, B D; Pepper, D S; Micklem, L R; Prowse, C V (Thrombosis and Haemostasis, 1987)
Murine monoclonal antibodies to human von Willebrand factor (vWf) were immobilised on Sephacryl S-1000. Various solutes were screened for their ability to elute 125 I-vWf from the immobilised antibodies. The most effective solutions were then tested to determine which allowed retention of factor VIII procoagulant activity (VIII: C) and activity of vWf measured by platelet aggregation in the presence of ristocetin (Ristocetin cofactor activity R.cof.). Finally, F VIII complex was purified from both plasma and cryoprecipitate by immunoaffinity chromatography under the selected conditions. The product had a specific activity of 45 units of VIII: C per mg of protein and 60 units of R. cof. per mg representing a 4000-fold purification from plasma. The fibrinogen and fibroneetin content were each less than 4% of the total protein with vWf accounting for 60% of the total protein in the final product. Multimer analysis of the product showed a similar pattern to normal plasma and contamination by murine monoclonal antibody was less than 300 ng per mg of protein. A novel product is thus obtained containing both clinically relevant VIII :C and R. cof. in a single vial whilst using only one specific monoclonal antibody.
Keywords: Factor VIII; Monoclonal antibody; Affinity chromatography